α1-Microglobulin Binds Illuminated Flavins and Has a Protective Effect Against Sublethal Riboflavin-Induced Damage in Retinal Epithelial Cells - Bergwik, Jesper; Åkerström, Bo (Frontiers in Physiology, 2020)
Riboflavin (vitamin B2) is an important constituent of the prosthetic groups flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN), which are utilized as electron-carriers in energy metabolism. Excitation by UV-light leads to the generation of riboflavin radicals and reactive oxygen species (ROS), which can oxidize a wide range of biomolecules. The human protein α1-microglobulin (A1M) is a reductase and a radical scavenger, which can protect cells and matrix against oxidative damage. Here, we provide evidence of a molecular interaction between illuminated riboflavin and A1M, similar to the radical scavenging reactions previously seen between A1M and other organic radicals. Binding between riboflavin and A1M was demonstrated by gel migration shift, UV-absorbance and fluorescence spectrum analysis. The reaction between A1M and UV-light illuminated riboflavin involved covalent modification of A1M and proteolytic release of an N-terminal part of the protein. Furthermore, A1M also inhibited the ROS-induced photoreduction reaction of riboflavin, in a reaction involving the free thiol group in position C34. Finally, the results show a protective effect of A1M, analyzed by gene expression rates of stress genes, against sublethal damage in retinal epithelial cells in culture. Together, our results suggest a new role of A1M as a scavenger of riboflavin radicals and ROS produced during illumination of riboflavin.